Current Practice and Barriers to an Early Antimicrobial Conversion from Intravenous to Oral among Hospitalized Patients at Jimma University Specialized Hospital: Prospective Observational Study - Alemseged Beyene Berha; Gizat Molla Kassie (Interdisciplinary Perspectives on Infectious Diseases)
Objective. The aim of the present study was to explore the current practice and its barriers to an early antimicrobial conversion from intravenous (IV) to oral (PO) therapy among hospitalized patients. Method. Hospital based prospective observational study was conducted to assess the practice of an early antimicrobial IV to PO conversion and its barriers using medical chart and case-specific physicians’ interviews, respectively, from February to September, 2014. Patient charts and medication records were reviewed for appropriateness of IV to PO conversion program every 24hrs using a pretested data collection abstraction format. Independent samples t-test was used to compare the duration of therapy and time to clinical stability between converted and nonconverted patients. Two-tailed P values of < 0.05 were regarded as statistically significant. Results. One hundred forty-two patients were included in the study, of whom two-thirds (67.6%) of the patients were eligible for IV to PO antimicrobial conversion. However, only 20.9% of patients’ timely conversion was made. A shorter duration of IV therapy was recorded for converted (2.80±1.87) versus nonconverted patients (8.50±6.32), (P=0.009). The most important barriers of not converting IV to PO in clinically stable patients were presence of comorbidity; clinicians perceived that the patient should always complete IV course of antimicrobials as a standard practice. Conclusion. Conversion from IV to PO antimicrobials was found to be unnecessarily delayed in a significant proportion of patients hospitalized with moderate to severe infection due to a range of different barriers. Addressing these issues has the potential to reduce inappropriate antimicrobial use and resistance.